Role of NRF2 in Pathogenesis of Alzheimer’s Disease - Ching-Tung Chu; Akira Uruno; Fumiki Katsuoka; Masayuki Yamamoto (Antioxidants)
Alzheimer’s disease (AD) is a polygenic, multifactorial neurodegenerative disorder and remains the most prevalent form of dementia, globally. Despite decades of research efforts, there is still no effective cure for this debilitating condition. AD research has increasingly focused on transcription factor NRF2 (nuclear factor erythroid 2-related factor 2) as a potential therapeutic target. NRF2 plays a crucial role in protecting cells and tissues from environmental stressors, such as electrophiles and reactive oxygen species. Recently, an increasing number of studies have demonstrated that NRF2 is a key regulator in AD pathology. NRF2 is highly expressed in microglia, resident macrophages in the central nervous system, and contributes to neuroinflammation, phagocytosis and neurodegeneration in AD. NRF2 has been reported to modulate microglia-induced inflammation and facilitate the transition from homeostatic microglia to a disease-associated microglia subset. Genetic and pharmacological activation of NRF2 has been demonstrated to improve cognitive function. Here, we review the current understanding of the involvement of NRF2 in AD and the critical role that NRF2 plays in microglia in the context of AD. Our aim is to highlight the potential of targeting NRF2 in the microglia as a promising therapeutic strategy for mitigating the progression of AD.